PERIODONTAL PLASTIC SURGERY: BASIC CONCEPTS - Soares, Kaio Henrique; Martins, Olga Beatriz Lopes; Leite, Mariana Botelho; Alves, Sâmia Francy Ferreira; Lopes, Maria Rita Lima; Santos, Jefferson Aguiar; Paulino, Gabriela Leite; Soares, Célio Leone Ferreira (Seven Editora, 2026)
Periodontal Plastic Surgery aims to correct gingival and mucogingival deformities, promoting aesthetic and functional improvement and greater patient comfort. Its main indications include coverage of gingival recessions, augmentation of keratinized gingiva, correction of interdental papillae, removal of aberrant frenula, and clinical crown lengthening. Techniques such as free gingival grafts, subepithelial connective tissue grafts, and displaced flaps show predictable results when associated with adequate planning and correct surgical and postoperative management.